2021
DOI: 10.31083/j.rcm2203092
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous morphine use in acute heart failure increases adverse outcomes: a meta-analysis

Abstract: Intravenous morphine is a controversial treatment for acute heart failure (AHF). This study aimed to evaluate and compare the efficacy of intravenous morphine treatment vs. no morphine treatment in AHF patients. Relevant research conducted before June 2020 was retrieved from electronic databases. One unpublished study of our own was also included. Studies were eligible for inclusion if they compared AHF patients treated with intravenous morphine and patients who did not receive morphine. This meta-analysis inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…If administered at all, clinicians should be alert to stop treatment very soon in case of unresponsiveness and severe adverse events. Of note, for acute HF, in 2021 alone, three large studies reported that the use of opioids led to increased mortality in this population 25–27. A recent study from Domínguez-Rodríguez et al 28 found that morphine, compared with midazolam, doubled the incidence of adverse events when used to treat breathlessness in patients with HF.…”
Section: Discussionmentioning
confidence: 99%
“…If administered at all, clinicians should be alert to stop treatment very soon in case of unresponsiveness and severe adverse events. Of note, for acute HF, in 2021 alone, three large studies reported that the use of opioids led to increased mortality in this population 25–27. A recent study from Domínguez-Rodríguez et al 28 found that morphine, compared with midazolam, doubled the incidence of adverse events when used to treat breathlessness in patients with HF.…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] Despite the theoretical benefits, lack of consensus and evidence on serious adverse events, it is still being used for APE, especially in patients with agitation and anxiety. [14,15] There is significant variation in practice with regard to clinical practice guidelines for APE. The American Heart Society and the American College of Cardiology advise against the routine administration of morphine, and only recommend morphine in patients receiving palliative care.…”
Section: Researchmentioning
confidence: 99%
“…They included seven studies (one RCT, one non-randomised control trial and five observational studies), and 150 639 participants. Lin et al [14] studied intravenous morphine in heart failure and reviewed five studies (three propensity-matched cohorts and two retrospective analyses (one unpublished) with 14 9967 participants. Zhang et al [34] investigated the safety of morphine in patients with acute heart failure, and included seven retrospective case-control studies and 172 226 participants, including adjusted measures of effect similar to Gao et al [7] The treatment given to control groups in included studies was not described (appendix: https://www.samedical.org/file/2059 shows tables of characteristics of included and excluded studies).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations